Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find the equation of the circle given the center [tex]\((-3.2, -2.1)\)[/tex] and the radius 4.3, we use the standard form of the equation of a circle:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
where [tex]\((h, k)\)[/tex] is the center of the circle and [tex]\(r\)[/tex] is the radius.
Given:
- The center [tex]\((h, k) = (-3.2, -2.1)\)[/tex]
- The radius [tex]\(r = 4.3\)[/tex]
We substitute these values into the standard form:
1. [tex]\(h = -3.2\)[/tex] and [tex]\(k = -2.1\)[/tex]
2. [tex]\(r = 4.3\)[/tex]
Thus, the equation becomes:
[tex]\[ (x - (-3.2))^2 + (y - (-2.1))^2 = (4.3)^2 \][/tex]
This simplifies to:
[tex]\[ (x + 3.2)^2 + (y + 2.1)^2 = 4.3^2 \][/tex]
Now, we match this equation to the given choices:
A. [tex]\((x+3.2)^2+(y-2.1)^2=4.3^2\)[/tex]
B. [tex]\((x-2.1)^2-(y+3.2)^2=(4.3)^2\)[/tex]
C. [tex]\((x+3.2)^2+(y+2.1)^2=(4.3)^2\)[/tex]
D. [tex]\((x+2.1)^2+(y-3.2)^2=4.3^2\)[/tex]
The correct equation that matches ours is:
C. [tex]\((x+3.2)^2+(y+2.1)^2=(4.3)^2\)[/tex]
Therefore, the correct choice is:
[tex]\[ \boxed{3} \][/tex]
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
where [tex]\((h, k)\)[/tex] is the center of the circle and [tex]\(r\)[/tex] is the radius.
Given:
- The center [tex]\((h, k) = (-3.2, -2.1)\)[/tex]
- The radius [tex]\(r = 4.3\)[/tex]
We substitute these values into the standard form:
1. [tex]\(h = -3.2\)[/tex] and [tex]\(k = -2.1\)[/tex]
2. [tex]\(r = 4.3\)[/tex]
Thus, the equation becomes:
[tex]\[ (x - (-3.2))^2 + (y - (-2.1))^2 = (4.3)^2 \][/tex]
This simplifies to:
[tex]\[ (x + 3.2)^2 + (y + 2.1)^2 = 4.3^2 \][/tex]
Now, we match this equation to the given choices:
A. [tex]\((x+3.2)^2+(y-2.1)^2=4.3^2\)[/tex]
B. [tex]\((x-2.1)^2-(y+3.2)^2=(4.3)^2\)[/tex]
C. [tex]\((x+3.2)^2+(y+2.1)^2=(4.3)^2\)[/tex]
D. [tex]\((x+2.1)^2+(y-3.2)^2=4.3^2\)[/tex]
The correct equation that matches ours is:
C. [tex]\((x+3.2)^2+(y+2.1)^2=(4.3)^2\)[/tex]
Therefore, the correct choice is:
[tex]\[ \boxed{3} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.